Museum Istiqlal dan Identitas Keislaman di Indonesia - Irmawati Marwoto Johan (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
Based on the concept of the new museology, a museum is seen to function as an educational institution that aims to increase and strengthen society’s awareness of its own identity so that it will realise the potenial for better development. Museum Istiqlal is a museum that represents Islamic identity in Indonesia and its goal is for the Museum to become a location where the community can learn more about this subject. The museum seeks to promote wider understanding about the variety of social and daily life in Islamic cultures in Indonesia, as well as about religious harmony, which is inclusive Islam, and also many other subjects.